Effect of Crude Protein Level and Coarse Wheat Bran on Nursery Pig Growth Performance - K. L. Batson; H. I. Calderón; M. D. Tokach; J. C. Woodworth; R. D. Goodband; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2020)
Two experiments were conducted to determine the effect of adding coarse wheat bran with reduced crude protein level in diets without pharmacological levels of zinc oxide on the growth performance and fecal dry matter of nursery pigs. Our objective was to determine if a low-crude protein diet with an added fiber source might provide similar growth performance and reduce the incidence of scours in weanling pigs compared to a typical, high-protein diet with added Zn. A total of 300 and 350 pigs (DNA 241 × 600), initially 15.4 and 13.7 lb body weight (BW), were used in Exp. 1 and 2, respectively. There were 5 pigs per pen and 12 and 14 replicates per treatment in Exp. 1 and 2, respectively. After weaning, pigs were fed a common pelleted diet with pharmacological levels (3,000 ppm Zn) of ZnO for 10 d in Exp. 1, and without pharmacological levels of ZnO for 14 d in Exp. 2. Then, pens were assigned to one of 5 dietary treatments in a randomized complete block design with BW as the blocking factor. In Exp. 1 and 2, treatment diets were offered in mash form and in one dietary phase. All dietary treatments contained 4% coarse wheat bran and consisted of: 1) positive control with ZnO (2,000 ppm Zn) and 21% crude protein (CP) formulated to 1.35% standardized ileal digestible (SID) lysine; 2) a diet with 110 ppm added Zn and 21% CP (1.35% SID lysine); 3) a diet with 110 ppm added Zn formulated to 18% CP (1.20% SID lysine); 4) an 18% CP diet with 110 ppm added Zn formulated to 1.35% SID lysine by the addition of feed grade amino acids; and 5) diet 4 with the addition of non-essential amino acids (glycine and glutamic acid). A common post-treatment pelleted diet was fed for 14 d in Exp. 2 but not in Exp. 1. Data were analyzed using the lmer function from the lme4 package in R. In Exp. 1, pigs fed diets with 21% CP had increased (P<0.05) ADG and heavier (P<0.05) final BW; however, treatment means did not separate when Tukey adjustment was applied during statistical analysis. Pigs fed diets with 21% CP had improved (P<0.05) feed efficiency similarly to pigs fed 18% CP diets with the addition of non-essential amino acids. During the experimental period in Exp. 2, pigs fed high CP diets with ZnO had increased (P<0.05) ADG compared to pigs fed the 18% CP diet with 1.2% SID lysine and the 18% CP diet with high levels of feed grade essential amino acids. Feed efficiency was improved (P<0.05) for pigs fed the 18% CP diet with added non-essential amino acids and for pigs fed both 21% CP diets compared to the other 18% CP diets without ZnO. Compared to pigs fed 18% CP diets, pigs fed diets with 21% CP had increased (P<0.05) d 13 BW. Visual fecal score was decreased (P<0.05) for pigs fed the 18% CP diets compared to pigs fed 21% CP without added ZnO in Exp. 1. Pigs fed the 21% CP diet without ZnO experienced increased (P<0.05) visual fecal score in Exp. 2. No evidence for differences in fecal dry matter were observed throughout either trial; however, when Exp. 1 and Exp. 2 were combined, increased (P<0.05) fecal dry matter was observed for pigs fed the 1.2% SID lysine diet compared to pigs fed 21% CP diets on d 6. Fecal dry matter was increased (P<0.05) on d 13 for pigs fed the reduced Lys (1.2% SID lysine) diet compared to pigs fed 21% CP without ZnO. In summary, results from these experiments suggest that reducing crude protein decreases growth performance compared to pigs fed high crude protein diets. Adding glycine and glutamine to the low CP diets improved feed efficiency, but not daily gain.
Keywords: crude protein; fecal dry matter; fiber; nursery pigs; zinc